PENERAPAN MODEL INKUIRI TERBIMBING DENGAN MEDIA KONKRET DALAM PENINGKATAN PEMBELAJARAN IPA TENTANG GAYA PADA SISWA KELAS V SDN 6 PANJER OLEH: DIAH KUMALA IZZA 1, TRIYONO 2, ROKHMANIYAH 3 PGSD FKIP UNIVERSITAS SEBELAS MERET, JL. KEPODANG 67 A PANJER, - Izza, Diah Kumala (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Guided Inquiry Models with Concrete Media in Improving Natural Science Learning about Force for the Fifth Grade Students of SDN 6 Panjer in Academic Year 2015/2016. The objective of this research is to  improve learning process and natural science learning outcomes about force in the fifth grade students of SDN 6 Panjer. This collaborative Classroom Action Research (CAR) was conducted in three cycles. Each cycle consists of two meetings. Each meeting consists of four stages: planning, action, observation, and reflection. The subjects were the fifth grade students of SDN 6 Panjer totaling 28 students. Data collection techniques used in this research are in the form of test and non-test. The validity of the data in this research applied triangulation of data sources and triangulation techniques. Techniques of analyzing data used descriptive qualitative data consisting of data reduction, data presentation, and drawing conclusion. The research was stopped after learning process and students' learning outcomes reached minimum completeness criteria of 75 for 85% of students. The result showed that the application of guided inquiry models with concrete media can improve learning process and natural science learning outcomes about force for the fifth grade students in SDN 6 Panjer.Keywords: guided inquiry, concrete media, learning, natural science Abstrak: Diah Kumala Izza. Penerapan Model Inkuiri Terbimbing dengan Media Konkret dalam Peningkatan Pembelajaran IPA tentang Gaya pada Siswa Kelas V SDN 6 Panjer. Tujuan penelitian ini adalah untuk meningkatkan proses dan hasil belajar IPA tentang gaya pada siswa kelas V SDN 6 Panjer. Penelitian Tindakan Kelas (PTK) kolaboratif ini dilaksanakan dalam 3 siklus. Setiap siklus terdiri dari dua pertemuan. Setiap pertemuan terdiri dari 4 tahapan yaitu: perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian ini adalah siswa kelas V SDN 6 Panjer yang berjumlah 28 siswa. Teknik pengumpulan data berupa teknik tes dan nontes. Validitas data pada penelitian ini menggunakan triangulasi sumber data dan triangulasi teknik. Analisis data menggunakan analisis data kualitatif deskriptif yang terdiri dari reduksi data, penyajian data, dan penarikan kesimpulan. Penelitian dihentikan setelah proses dan hasil belajar siswa mencapai KKM = 75 sebanyak 85% siswa. Hasil penelitian menunjukkan bahwa penerapan model inkuiri terbimbing dengan media konkret dapat meningkatkan proses dan hasil belajar IPA tentang gaya pada siswa kelas V SDN 6 Panjer.Kata Kunci: inkuiri terbimbing, media konkret, pembelajaran, IPA